Detection of a novel haemoplasma species in fattening pigs with skin alterations, fever and anaemia. (1st July 2020) - Stadler, Julia; Ade, Julia; Ritzmann, Mathias; Hoelzle, Katharina; Hoelzle, Ludwig E
Abstract : Background: In a fattening farm in Southern Germany, skin alterations (urticaria, haemorrhagic diathesis) and high fever were observed in 30% of the pigs 2 weeks after arrival. Feed intake was severely compromised in affected pigs. Methods: After detailed clinical observation, blood samples from affected pigs were collected for haematological, PCR and serological investigations. In addition, pathological investigations were performed on one pig. Results and conclusion: Analysis of blood parameters revealed a normocytic, normochromic anaemia. A novel porcine haemoplasma species was detected in blood samples of affected pigs and spleen sample of the necropsied pig by PCR. Phylogenetic analyses based on the 16S rDNA showed 99% identity to a novel porcine haemoplasma (' Candidatus ( Ca .) M. haemosuis') species which has recently been described in China. Interestingly, this is the first report of ' Ca . M. haemosuis' in pigs with clinical signs resembling those of Mycoplasma (M) suis and the first description of this novel haemoplasma species outside Asia. On‐farm affected pigs were treated with oxytetracycline and non‐steroidal anti‐inflammatory drugs. Clinical signs improved after implementation of treatment and optimisation of management procedures. This case might indicate that other porcine haemoplasma species than M suis can induce fever and skin alterations and may have an economic impact on affected farms.